Female Intimate Partner Violence Survivors’ Experiences With Disclosure to Informal Network Members - Johnson, Ingrid Diane (Journal of interpersonal violence, 2021)
With the growing recognition of the importance of disclosure to informal network members (INMs) in shaping experiences for survivors of intimate partner violence (IPV), numerous quantitative studies have examined these processes, but have not provided detailed descriptive analyses of the disclosure process. Yet, these descriptive data can be a rich contribution in their own right given the dearth of knowledge about IPV disclosure. This article presents in-depth descriptive data on a Mid-Atlantic metropolitan area sample of 200 female IPV survivors’ experiences with disclosure to their INMs (collected using a one-time, online survey). Most survivors (66%) disclosed to at least one INM during their initial violent relationship. The three most commonly experienced reactions to disclosure were INMs listening to the survivors’ feelings, urging the survivors to talk about how they felt, and expressing that the violent partners’ behaviors were problematic. The three least commonly experienced reactions were INMs blaming survivors or saying that they deserved to be treated that way, offering financial assistance, and telling them to stop talking about the incident(s). Among survivors who disclosed to their INMs, 93.9% agreed that disclosure to their INMs helped them in some way. Survivors had disclosure experiences that were relatively comparable with other survivor samples, indicating good external validity. The findings regarding reactions to disclosure were also comparable with previous studies, although the extant published literature was quite limited. Young female survivors experience a variety of reactions from their INMs, most often experiencing supportive and subjectively “positive” reactions. As the research delving into the influences and impacts of disclosure expands, close attention should be paid to how these variables are being collected and disseminated so that we have a better understanding of what happens during disclosure to INMs.